Financial Security Assessment in the European Union Countries - Grikietytė-Čebatavičienė, Jurga (Vilnius University Open Series, 2021)
Financial security of the country means the absence of threats to the financial system, ensuring the stability and development of the financial system and the ability to maintain the financial sovereignty of the state. The aim of the article is to evaluate financial security in EU countries. The aggregate financial security index (AFSI) is used to reach this goal. AFSI calculation is based on five sub-indexes: Human Development Index, Economic Globalisation Index, Financial Development Index, Index of Economic Freedom and Country Level Index of Financial Stress. The results show that Market-based EU countries have the highest financial security. The lowest financial security was set in Eastern European countries.